The Pengaruh kemampun TIK pengalaman mengajar, motivasi kerja terhadap kompetensi profesional guru SMK Negeri Jeneponto: Influence of ICT Skills, Teaching Experience, and Work Motivation on the Professional Competence of Teachers at Jeneponto Public Vocational High Schools - Fitri Wahyuni; Sapto Haryoko; Anas Arfandi (UNM Journal of Technology and Vocational, 2024)
This study aims to explore the influence of ICT skills, teaching experience, and work motivation on the professional competence of teachers in State Vocational Schools (SMK) in Jeneponto. With a quantitative method and descriptive approach, 90 teachers were randomly selected from several vocational schools in the area. Research instruments included multiple-choice tests to measure ICT skills and professional competence, as well as expert judgment for teaching experience, and questionnaires for work motivation. Data analysis was conducted using multiple regression techniques. The results indicate that ICT skills significantly affect the professional competence of teachers in SMK Negeri Jeneponto (t-value > critical t-value; 9.892 > 1.66). However, there is no significant influence of teaching experience and work motivation on professional competence individually (t-value < critical t-value; 0.519 < 1.66; 0.510 < 1.66). Nevertheless, collectively, ICT skills, teaching experience, and work motivation significantly influence professional competence (F-value > critical F-value; 36.60 > 2.32), with a contribution of 54%, indicating the importance of these factors in improving the quality of teaching in SMK. The implication of this research is the necessity of institutional support in enhancing teacher resources, particularly in ICT training and the development of work motivation, to improve their professional competence. This can help enhance the quality of education in SMK Negeri Jeneponto and promote better learning outcomes for students.